Dendrobium huoshanense polysaccharide regulates intestinal lamina propria immune response by stimulation of intestinal epithelial cells via toll-like receptor 4. (15th October 2019) - Xie, Song-Zi; Shang, Zhen-Zi; Li, Qiang-Ming; Zha, Xue-Qiang; Pan, Li-Hua; Luo, Jian-Ping
Graphical abstract: GXG could directly interact with IECs through TLR4 and stimulate IECs to secret the cytokines including IL-6, MCP-1 and CINC-1, which further effectively regulate the production of cytokines and functionally development of immune cells in LPCs. Highlights: D. huoshanense polysaccharide (GXG) stimulated intestinal epithelial cells (IECs) to induce immune response in lamina propria cells (LPCs). Cytokines secreted from GXG-stimulated IECs induced immune responses in LPCs. TLR4 is responsible for GXG binding to IECs. TLR4 mediated GXG-stimulated IECs to regulate the immune response of LPCs. Abstract: A homogenous polysaccharide (GXG) from Dendrobium huoshanense with stable digestive behavior and effective immunoregulatory function was employed to explore its underlying molecular basis regulating intestinal mucosal immune response from the view of interaction between GXG and intestinal epithelial cells (IECs). Using in vitro establishedco- culture system consisting of IECs and lamina propria cells (LPCs), we found the immune response of LPCs could be effectively regulated by GXG-stimulated IECs, and three cytokines including IL-6, MCP-1 and CINC-1 produced from GXG-stimulated IECs were the main factors involved in modulating immune response of LPCs. Toll-like receptor 4 (TLR4) was identified as an essential receptor for IECs to directly bind GXG. Receptor intervention experiments demonstrated that TLR4 mediated GXG-induced activation of IECs, which further induces immunomodulating effects on LPCs. These results suggest that GXG could modulate the immune response in LPCs by the direct interaction with IECs via TLR4.